A REVIEW OF ACYRANTHES ASPERA (Journal of Pharmaceutical Negative Results, 2023)
For hundreds of years, plants have been used by humans as a medicine to treat different ailments. In ancient Ayurveda and Unani medicine, there exists a plethora of knowledge and information and benefits of herbal drugs. Achyranthes aspera is a very potential indigenous herbal plant which is found in South America, Asia and Africa and is usually found as weed. Various parts of Achyranthes aspera have been used traditionally as a cure for various diseases, which has been discussed in this review article. Achyranthes aspera contains wide range of chemical constituents such as terpenoids, alkaloids, steroids, saponins and flavonoids. In this paper, the phytochemicals present in various parts of Achyranthes aspera, traditional uses as well as pharmacological properties of Achyranthes aspera has been reviewed and explained.